Law on Interfaith Marriage Perspective of Al-Quran Education on Indonesian Government Regulations and Legislation - Muchtarom (The International Journal of Law Review and State Administration, 2024)
This research aims to analyze. M. Quraish Shihab and Al-Maraghi's interpretation of interfaith marriages. The relevance of interpreting interfaith marriages according to M. Quraish Shihab and Al-Maraghi. The research method with a qualitative approach describes the findings that occurred. Data Analysis Techniques use (1). Content analysis is an in-depth discussion of written information in mass media. (2). Using a comparative method, By comparing (1). Tafsir M. Quraish Shihab and Al-Maraghi regarding interfaith marriages (a). The marriage of Muslim men and women of the People of the Book, and both are permitted. (b) The marriage of Muslim women to Muslim men and People of the Book is haram (2) The relevance of M. Quraish Shihab and Al-Maraghi regarding interfaith marriages in Indonesian law (a). The marriage of a Muslim man to an Ahl al-Kitab woman is not relevant to article no. 1 of 1974. KHI article 2 paragraph (1) and 1 of 1991 Articles 4, 40, 44 and 61 concerning Marriage (b) Marriage of Muslim men with polytheist women, relevant article No. 1 of 1974. KHI article 2 paragraph (1 ) No1 of 1991 Articles 4, 40, 44 and 61 marriage Marriage (c). The marriage of a Muslim woman to a Mushrik man and an Ahl Book is relevant to article no. 1 of 1974. KHI article 2 paragraph (1) Number 1 of 1991 Articles 4, 40, 44 and 61 concerning Marriage